Analisis Niat Nasabah Bank Syariah untuk Menggunakan Mobile Banking - Sudarsono, Heri (Jurnal Ilmiah Poli Bisnis, 2022)
This study aims to analyze the factors that influence the intention of Islamic bank customers to use mobile banking. This study uses the Unified Theory of Acceptance An Use of Technology (UTAUT) as the main reference in building the model in this study. Respondents were obtained through the distribution of questionnaires in the form of google forms in a number of WhatsApp, Facebook and Instagram groups. The number of respondents who meet the criteria for Muslim customers who have accounts at Islamic banks is 376 people, consisting of 226 men and 150 women. Hypothesis testing was carried out using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results of data processing show that the variables of performance expectancy, effort expectancy, and facilitating conditions have a positive effect on the behavioral intention of Islamic bank customers to use mobile banking. On the other hand, social influence does not affect the customer's intention to use mobile banking. The implication of this result is that Islamic bank management needs to maximize supporting facilities by adding a number of mobile banking features that suit customer needs.